Transpinal and Transcortical Stimulation Alter Corticospinal Excitability and Increase Spinal Output - Knikou, Maria (Public Library of Science, 2014)
The objective of this study was to assess changes in corticospinal excitability and spinal output following noninvasive transpinal and transcortical stimulation in humans. The size of the motor evoked potentials (MEPs), induced by transcranial magnetic stimulation (TMS) and recorded from the right plantar flexor and extensor muscles, was assessed following transcutaneous electric stimulation of the spine (tsESS) over the thoracolumbar region at conditioning-test (C-T) intervals that ranged from negative 50 to positive 50 ms. The size of the transpinal evoked potentials (TEPs), induced by tsESS and recorded from the right and left plantar flexor and extensor muscles, was assessed following TMS over the left primary motor cortex at 0.7 and at 1.1× MEP resting threshold at C-T intervals that ranged from negative 50 to positive 50 ms. The recruitment curves of MEPs and TEPs had a similar shape, and statistically significant differences between the sigmoid function parameters of MEPs and TEPs were not found. Anodal tsESS resulted in early MEP depression followed by long-latency MEP facilitation of both ankle plantar flexors and extensors. TEPs of ankle plantar flexors and extensors were increased regardless TMS intensity level. Subthreshold and suprathreshold TMS induced short-latency TEP facilitation that was larger in the TEPs ipsilateral to TMS. Noninvasive transpinal stimulation affected ipsilateral and contralateral actions of corticospinal neurons, while corticocortical and corticospinal descending volleys increased TEPs in both limbs. Transpinal and transcortical stimulation is a noninvasive neuromodulation method that alters corticospinal excitability and increases motor output of multiple spinal segments in humans.